Intrageneric relationships within Gerbilliscus (Rodentia, Muridae, Gerbillinae), with characterization of an additional West African species - Granjon, Laurent; Colangelo, Paolo; Tatard, Caroline; Colyn, Marc; Dobigny, Gauthier; Nicolas, Violaine (Zootaxa, 2012)
The systematics of the African rodent genus Gerbilliscus is still a matter of debate. At the genus level it has been said toinclude the related genus Gerbillurus, and at the species level some species still need to be definitely recognized as dis-tinct. To tackle these questions, we gathered and analyzed mitochondrial (cytochrome b) and nuclear (BRCA1) gene se-quences in a number of specimens representing ten species of Gerbilliscus and three species of Gerbillurus. Phylogeneticreconstructions confirm that Gerbillurus should be considered a synonym of Gerbilliscus. They also clearly show that spe-cies diversity in this group is spatially organized, with geographically well-defined species groups covering major areasof sub-Saharan Africa, namely Southern, Eastern and Western Africa. In the latter area, a well-supported genetic lineageappears to correspond to a hitherto overlooked species, also characterized by a distinctive karyotype. This species is char-acterized by an overall large size, a relatively long tail, a distinct karyotype, and represents a well-differentiated geneticcluster. It ranges from Benin to Guinea in Sudano-Guinean forest-savanna mosaic habitats, where it can be sympatric withthe congeneric species G. kempi and G. guineae. Detailed body and skull morphological and biometrical analyses per-formed on samples of the West African species, including type specimens described in this region, suggest that this speciesmay correspond to G. kempi. If confirmed, this would imply that what is currently named G. kempi would deserve another species name, the most likely of which would be G. giffardi.